FACTORS AND DETERMINANTS OF HIGH BLOOD PRESSURE AMONG AGE GROUPS IN MOSUL - H. Eefan, Abdalrahim (Academia Open, 2026)
<div class="text-base my-auto mx-auto [–thread-content-margin:var(–thread-content-margin-xs,calc(var(–spacing)*4))] @w-sm/main:[–thread-content-margin:var(–thread-content-margin-sm,calc(var(–spacing)*6))] @w-lg/main:[–thread-content-margin:var(–thread-content-margin-lg,calc(var(–spacing)*16))] px-(–thread-content-margin)"> <div class="[–thread-content-max-width:40rem] @w-lg/main:[–thread-content-max-width:48rem] mx-auto max-w-(–thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" data-message-author-role="assistant" data-message-id="0b9b3a6c-fda6-419e-aeee-e3dcd363f1d0" data-message-model-slug="gpt-5-3"> General Background: Hypertension is a major global health problem characterized by increased arterial pressure resulting from multiple behavioral, physiological, and pathological factors. Specific Background: In Mosul, limited recent epidemiological data exist, particularly among younger populations under 50 years of age diagnosed with hypertension. Knowledge Gap: There is insufficient localized evidence regarding dominant determinants and patient behavior related to hypertension management in this age group. Aims: This study aimed to estimate the prevalence of hypertension among individuals under 50 in Mosul and to identify its main causes and management approaches. Results: Among 250 patients, hypertension was most prevalent in the 30–40 age group (49%). The leading determinants were psychological stress and difficult economic conditions, followed by kidney disease, obesity, smoking, and family history. Lifestyle modifications primarily included dietary changes (40%) and physical activity (30%), while treatment adherence varied, with only 52% taking medication regularly. Novelty: This study highlights the dominant role of socioeconomic hardship and psychological stress as primary contributors to hypertension in a younger population. Implications: These findings emphasize the need for targeted public health strategies addressing social conditions, stress management, and improved treatment adherence to control hypertension in similar populations. Highlights • Psychological burden and financial constraints emerge as dominant determinants • Highest proportion observed in individuals aged 30–40 years • Medication adherence remains inconsistent among diagnosed patients Keywords Hypertension; Psychological Stress; Socioeconomic Status; Young Adults; Lifestyle Modification